Die onderrig van enkele aspekte van elementere algebra in standerd vyf : 'n onderrigeksperiment - Joubert, I. H.(Isabella Helena) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M. Ed.) -- Universiteit van Stellenbosch, 1989.